Turn-off-the-Month Effect on Stocks in LQ45 Index and Various Sectors in the Indonesia Stock Exchange using GARCH (p,q) - Pandekar, Galih; Putrini, Nadia (The Indonesian Capital Market Review, 2012)
There are few types of anomalies that occur in the Indonesia Stock Exchange, for example monthly effect, day-of-the-week effect, January effect, holiday effect, and turn-of-the-month effect. The existence of these anomalies is in contrast to the efﬁcient market hypothesis theory, due to a signiﬁ-cant difference in returns during certain periods. By using time-series analysis and the GARCH(p,q) method, the existence of the turn-of-the-month effect has been found in the Jakarta Composite Index, sectoral indexes, and stocks in LQ45. The turn-of-the-month effect seems to be seen in the last two days and the four previous days of each month. The January effect does not incite the turn-of-the-month effect. The turn-of-the-month effect appears due to an increasing volume of stocks acquired by investment managers who want to see their portfolio performance better.